Modeling Communication Networks and Protocols Implementation via the SMURPH System - Gburzyński, Paweł; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an introduction to the software system SMURPH, comprising a programming language, its compiler, and an execution environment, for specifying communication networks and protocols and executing those specifications in virtual worlds mimicking the behavior of real-life implementations. It particularly focuses on SMURPH's wireless modeling capabilities. Written in a manual-like fashion, it includes a comprehensive description of SMURPH functionality, as well as illustrations and case studies to aid understanding. .
Keywords: Telecommunication; Computational intelligence; Artificial intelligence; Communications Engineering, Networks; Computational Intelligence; Artificial Intelligence